2017
DOI: 10.1021/acs.energyfuels.7b03105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Gases on Elemental Mercury Removal in an Oxy-fuel CO2 Compression Process

Abstract: Oxy-fuel combustion is considered as one of the most promising options for capturing CO2 from coal-fired power plants. Oxy-fuel flue gas contains traces of gaseous elemental mercury (Hg0) impurity, which accumulate in the CO2 compression units, causing severe damage to the aluminum heat exchangers. It is of great interest that the co-capture of flue gas impurities, such as nitrogen oxide (NO x ) and elemental mercury, could be achieved in a CO2 compression system at a high pressure. Currently, most of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Absorption, , adsorption, , chemical looping combustion (CLC), , membranes separation, , and cryogenic distillation are well considered as effective methods to isolate CO 2 from the atmosphere. Among them calcium looping (CaL), a typical absorption technique, has been considered as one of the most important technologies for CO 2 isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Absorption, , adsorption, , chemical looping combustion (CLC), , membranes separation, , and cryogenic distillation are well considered as effective methods to isolate CO 2 from the atmosphere. Among them calcium looping (CaL), a typical absorption technique, has been considered as one of the most important technologies for CO 2 isolation.…”
Section: Introductionmentioning
confidence: 99%
“…However, Hg 0 is very difficult to be removed by current air pollution control devices (APCDs), because it has high volatility and low water solubility . Thus, the development of Hg 0 control technology is the essential problem to solve, especially for an oxy-fuel combustion system …”
Section: Introductionmentioning
confidence: 99%
“…also summarized recent work on mercury removal by modified adsorbents with a literature review. However, research into mercury control by activated carbon under oxy‐fuel combustion is still lacking in published reports . Note that H 2 O and SO 2 are much higher than those in air combustion due to the recycled flue gas, but there is little reported research into this.…”
Section: Introductionmentioning
confidence: 99%
“…However, research into mercury control by activated carbon under oxy-fuel combustion is still lacking in published reports. [17][18][19] Note that H 2 O and SO 2 are much higher than those in air combustion due to the recycled flue gas, 20 21 investigated the impact of H 2 O and other flue gases on mercury removal performance by sulfur-modified activated carbon under laboratory conditions. The results indicated that the sulfur-modified sorbent had greater mercury capacity than the raw sorbent, and the mechanism of Hg removal performance without H 2 O was different from that with H 2 O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation